(3GdaSGO GdEOGQj h GdeGdj (B:s (3h CKGQg GdGbJUGOjI h GdGLJeGYjI (B/s - (3GdTeQj, gGTes; (3GdaJdj, GjKGQ s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3GdGWGQ GdeaGgjej ddaSGO GdGOGQj h GdeGdj h eSHHGJ h CfhGYg h eXGgQg h GdJWhQ GdJGQjNj dg , GdJCKjQGJ h GdJcGdHa GdfGLeI Yf GdaSGO GdGOGQj h GdeGdj aj GdJfejI , JMdjd gPG GdaSGO aj Xd GdJWhQGJ GdGbJUGOjI GdOhdjI , , hGbY gPG GdaSGO aj cd ef (B: (3GdYQGb , fjLjQjG h SfZGahQI (B.s
(3agGQS U(B.7(3;eQGLY U(B.245 (3; edGMb U(B.221s
Keywords: (3GdaSGOs; (3GdaSGO GdGOGQjs; (3GdaSGO(B- (3GdeGdjIs